2019
DOI: 10.1016/j.physd.2019.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Hole-closing model reveals exponents for nonlinear degenerate diffusivity functions in cell biology

Abstract: Continuum mathematical models for collective cell motion normally involve reaction-diffusion equations, such as the Fisher-KPP equation, with a linear diffusion term to describe cell motility and a logistic term to describe cell proliferation. While the Fisher-KPP equation and its generalisations are commonplace, a significant drawback for this family of models is that they are not able to capture the moving fronts that arise in cell invasion applications such as wound healing and tumour growth. An alternative… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 57 publications
(85 citation statements)
references
References 57 publications
2
83
0
Order By: Relevance
“…For instance, the asymptotic analysis performed in this work can be extended to include higher-order terms. Another possible extension could be to consider generalizing the nonlinear degenerate diffusivity function to D(u) = u n , for some constant n > 0 [6,10,17,19,26]. We leave both extensions for future consideration.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the asymptotic analysis performed in this work can be extended to include higher-order terms. Another possible extension could be to consider generalizing the nonlinear degenerate diffusivity function to D(u) = u n , for some constant n > 0 [6,10,17,19,26]. We leave both extensions for future consideration.…”
Section: Discussionmentioning
confidence: 99%
“…(2) can be written as D (u ) = D u/K , and since D (0) = 0, this leads to the formation of sharp fronts [42,43], as we see in the experimental images in Figure 1. Previous studies that have compared the performance of the Porous-Fisher model to the Fisher-Kolmogorov model have often observed that the Porous-Fisher model provides a better description of various types of in vitro experiments [30,35,31].…”
Section: Cellular Reaction-diffusion Model Of Tissue Growthmentioning
confidence: 99%
“…This kind of assumption is one way to motivate the use of the Porous-Fisher model. Other arguments have been used to support the use of the Porous-Fisher model include arguments based on: (i) heuristic reasoning about the role of crowding-induced directed motion [32]; (ii) effects of cell-to-cell crowding and cell shape [34,49]; (iii) or geometric arguments relating to asymptotic observations of hole-closing near to the time of closure [31]; and (iv) heuristic arguments about the observation of sharp fronts in experimental images [27,28].…”
Section: S2 Mathematical Model Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Other variations include: (i) considering models with nonlinear diffusivity [28,29,30,31,32,33]; (ii) incorporating different nonlinear transport mechanisms [34,35,36]; (iii) models of multiple invading subpopulations [31,37]; and (iv) multi-dimensional models incorporating anisotropy [38]. The Fisher-KPP model gives rise to travelling wave-like solutions that do not allow the solution to go extinct.…”
Section: Introductionmentioning
confidence: 99%